Analisis Kualitas Layanan Hotel New Sany Rosa Bandung - Elisabeth, Elisabeth (Business Administration Study Program - Universitas Katolik Parahyangan, 2013)
In this decade, hospitality is an industry that grows rapidly in Indonesia, notably inBandung. New Sany Rosa Hotel Bandung is among the most popular hotels. Fac-ing tough industry, transformation at this hotel was enforced. The new managementdelivered a change in customer satisfaction valuation, from suggestions or criticsto service quality. The objective is to identify if five dimensions of service qualityimpact the customer satisfaction and which dimension has most influence on cus-tomer satisfaction. Interview was conducted and questionnaires were disseminatedto a hundred guests who stayed overnight. Result indicates that tangibility, empathy,reliability, responsiveness, and assurance have simultaneously and partially affectedthe satisfaction. Empathy is a dimension that influenced the customer satisfaction atthis hotel the most.Keywords: service quality, tangibles, empathy, reliability, responsiveness, assur-ance, customer satisfaction